2013
DOI: 10.1016/j.meegid.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The myxovirus resistance A (MxA) gene −88G>T single nucleotide polymorphism is associated with prostate cancer

Abstract: Background Myxovirus (influenza virus) resistance A (MxA) is an interferon stimulated antiviral protein that is required for a complete antiviral response. MxA polymorphism (rs2071430) is located within an Interferon Stimulated Response Element (ISRE) at position −88 in the gene’s promoter region, and it has been associated with increased susceptibility to infections and various diseases. In general, the low promoter activity genotype (GG) promotes susceptibility, whereas the high promoter activity genotype (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Alternatively, the overall low expression of MxA in prostate cancer could possibly be due to the polymorphism in the proximal promoter region of MxA. Our previous study established an association of MxA with prostate cancer risk, specifically the genotype with low promoter activity (25) which results in reduced expression of MxA. Alternatively, MxA gene could be deleted in prostate cancer as a consequence of TMPRSS2-ERG fusion in aggressive and invasive prostate cancer (8).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the overall low expression of MxA in prostate cancer could possibly be due to the polymorphism in the proximal promoter region of MxA. Our previous study established an association of MxA with prostate cancer risk, specifically the genotype with low promoter activity (25) which results in reduced expression of MxA. Alternatively, MxA gene could be deleted in prostate cancer as a consequence of TMPRSS2-ERG fusion in aggressive and invasive prostate cancer (8).…”
Section: Discussionmentioning
confidence: 99%
“…acknowledged to be involved in intracellular vesicle tra cking and organelle homeostasis, which chie y participates in the cellular antiviral response against a wide range of RNA viruses, including in uenza viruses and members of the bunyavirus family [51]. It is an interferon stimulated antiviral protein that is required for a complete antiviral response [52]. Preceding study found that down-regulation of MxA in LNCaP cells by dihydrotestosterone suggests that MxA appears to be meaningfully associated with cell cycle and further cancer development while the loss of MxA expression leads to increased metastasis and decreased sensitivity to Docetaxel, which shows that MxA expression could regulate the outcome of chemotherapy [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…When IL-1β increases in the serum of HCV patients, consequently, the response to IFN-based therapy significantly decreases (66 …”
Section: Il-1βmentioning
confidence: 99%
“…These SNPs have a major role on expression level of IL-10 gene. Therefore, lowering IL-10 expression drives immune system to Th1 type, which results in high-sustained viral clearance (66,71). Most patients with low expression of IL10 are at high risk of rejection in liver transplantation whereas a polymorphism named RA-rs9610 A/G which lowers IL-10 expression shows a significant relation to HCV outcome (74).…”
Section: Il-10mentioning
confidence: 99%